impact of work-family conflict and job stress on seafarer performance - Umi Rusilowati; Wawan Helmawan (Keberlanjutan)
Due to prolonged absences from family, seafarers face challenges that can lead to work-family conflict and job stress, potentially hindering their productivity at sea. We employ a quantitative study that surveyed 150 PT Jasindo Duta Segara seafarers using a Likert scale and purposive sampling to investigate these effects. Data analysis was conducted using structural equation modeling. The results reveal a significant negative impact of both work stress and family-work conflict on the performance of PT Jasindo Duta Segara seafarers. This research highlights the importance of addressing work-life balance concerns for seafarers to optimize their productivity. Future studies could explore targeted interventions to mitigate stress and family conflict, potentially improving seafarer performance and overall well-being.